Convection heat transfer in enclosures with inner bodies: A review on single and two-phase nanofluid models - Alsabery, Ammar I.; Abosinnee, Ali S.; Al-Hadraawy, Saleem K.; Ismael, Muneer; Fteiti, Mehdi A.; Hashim, Ishak; Sheremet, Mikhail A.; Galambaz, Mohammad; Chamkha, Ali J. (Renewable and sustainable energy reviews)
This review peruses a comprehensive implementation of inner bodies involved in cavities filled with regular and nanofluids for both natural and mixed convection modes. The topic of nanofluid acquired its importance in the heat transfer field about two decades ago. Many experimental studies have been conducted to establish accurate correlations between the nanoparticle's specifications (volume fraction, size, shape, and type) and the thermophysical properties (such as dynamic viscosity and thermal conductivity). However, most of the theoretical investigations focused on the use of nanoparticles in various geometrical conduits and enclosures. The review covers the implementation of nanofluid in cavities involving inner bodies using single and two-phase models. It is found that about 34% of the total reviewed studies have considered the nanofluid inside the cavities involving inner cylinders. The authors of this review have concluded that the extra numerical cost of the two-phase models has curbed the researcher's use of the single-phase model. It is found that the studies that adopt the two-phase model are only 19% of the total nanofluid studies. The two-phase model gave an essential detail about the collection of the nanoparticles on the surfaces of the inner bodies (primarily stationary bodies) and the segments of the undulations of wavy walls of the cavities. This phenomenon lowers the exchange of heat transfer.